Patient adherence and diabetes distress on glycemic outcomes: a cross-sectional study - Rahmatulloh, Wahyu; Ristiyorini, Iin; Kusumaningsih, Wiji Sri; Ainni, Ayu Nissa; Zakhroh, Siti Aminatun (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2024)
Background: Diabetes Mellitus (DM) is a chronic disease that requires high compliance with therapy and lifestyle changes. However, compliance often causes emotional stress that can affect the effectiveness of treatment. This study is important to understand the impact of medication compliance and diabetes distress on glycemic control in DM patients.Purpose: This study aims to determine the impact of adherence and distress on glycemic control.Methods: This cross-sectional study was conducted at the Kebumen II Health Center from April to July 2024 with a sample of 87 respondents. The Diabetes Distress Scale (DDS) was used to measure patient stress levels, and the Medication Adherence Report Scale (MARS-5) was used to assess patient compliance levels. while glycemic control was evaluated with random blood glucose (RBG) and fasting blood glucose (FBG). Data were analyzed using the Pearson correlation test.Results: His study was dominated by female participants (75%) and those over 60 years of age (51%). A total of 64% of patients showed low adherence to antidiabetic medication, and 78% had uncontrolled random blood glucose (RBG) levels. Moderate diabetes distress was observed in 36% of patients, while 46% experienced low distress. There was a significant relationship between medication adherence and RBG levels (r =-0.283; p<0.05), but no significant relationship with FBG. There was no significant relationship between diabetes distress and blood glucose levels (RBG and FBG).Conclusion: Low adherence levels will significantly increase RBG levels but not significantly increase FBG levels. Likewise, high stress has the potential to increase blood glucose levels, although not statistically significant.